Low-Vacuum Catalyst-Free Physical Vapor Deposition and Magnetotransport Properties of Ultrathin Bi2Se3 Nanoribbons - Raitis Sondors; Kiryl Niherysh; Jana Andzane; Xavier Palermo; Thilo Bauch; Floriana Lombardi; Donats Erts (Nanomaterials, 2023)
In this work, a simple catalyst-free physical vapor deposition method is optimized by adjusting source material pressure and evaporation time for the reliable obtaining of freestanding nanoribbons with thicknesses below 15 nm. The optimum synthesis temperature, time and pressure were determined for an increased yield of ultrathin Bi2Se3 nanoribbons with thicknesses of 8–15 nm. Physical and electrical characterization of the synthesized Bi2Se3 nanoribbons with thicknesses below 15 nm revealed no degradation of properties of the nanoribbons, as well as the absence of the contribution of trivial bulk charge carriers to the total conductance of the nanoribbons.